Pengaruh Lingkungan Kerja Terhadap Semangat Kerja Pegawai pada Pemerintahan Desa Peninjauan Kecamatan Maro Sebo Ulu Kabupaten Batanghari Provinsi Jambi - Nasrul; Mulia Indah Purwati; Jumisar; Seno Aji (LPPM Universitas Adiwangsa Jambi, 2022)
This research aims to determine the influence of Knowing the influence of the work environment on employee morale in the Pengunjungan Village Government, Maro Sebo Ulu District, Batanghari Regency, Jambi Province. The research method used in this research simple regression analysis analysis techniques. The results of the research show that work environment and employee morale have a positive influence on in the Pengunjungan Village Government, Maro Sebo Ulu District, Batanghari Regency, Jambi Province.